Politik Hukum Pengaturan Masyarakat Hukum Adat (Studi Putusan Mahkamah Konstitusi) - Zayanti Mandasari (Jurnal Hukum IUS QUIA IUSTUM, 2014)
This study discussed the problem of the indigenous law community existence in Indonesia, and the dynamics of the indigenous law community viewed from the Acts of Constitutional Court. This study was focused to analyze two matters, namely: First, how is the existence of the indigenous law community in Indonesia? Second, how does the indegenous law community take the Acts of Constitutional Court? This study used the statute approach. In addition, case study approach was also used to find the ratio decidendi used by the judges of Constitutional Court in adjudicating the statute test case related to the indigenous law community. The result of the research concluded that: first, the existence of the indigenous law community in Indonesia had already been accomodated in the prevailing laws of regulations including the 1945 Constitution of Republic Indonesia, Acts, Regional Regulations, Governors’ Decrees, and Heads of Regions’ Decrees. Second, the law politics of the indigenous law community took the Acts of Constitutional Court as strengthening the existence of the indigenous law community in Indonesia by providing the interpretation or explanation.